Politik Hukum Pidana Mati dan Upaya Perlindungan Hak Hidup di Indonesia: Perspektif UU Nomor 1 Tahun 2023 - Putra, Alif Arhanda (SIGn Jurnal Hukum, 2025)
The regulation of capital punishment within the Indonesian legal system presents a fundamental tension with the constitutional guarantee of the right to life. Law Number 1 of 2023 introduces a new formulation necessitating an in-depth analysis of its underlying policy background and inherent protection mechanisms. This research aims to analyze the legal policy underpinning the capital punishment provisions in Law Number 1 of 2023 and to identify and analyze the forms of protection for the right to life within its application mechanism. Utilizing a normative legal research method with statute and conceptual approaches, this study qualitatively and interpretively examines relevant primary and secondary legal materials. The analysis indicates that the legal policy on capital punishment in Law Number 1 of 2023 constitutes a compromise-based "middle path policy" between retentionist views and the strengthening of human rights norms, retaining the sanction as a last resort (ultimum remedium) with a mandatory 10-year probationary mechanism. The primary form of protection for the convict's right to life manifests through this conditional mechanism, which normatively provides execution postponement and opens the possibility of commutation. Nevertheless, the effectiveness of this protection is limited by potential subjectivity in the commutation evaluation criteria and discretionary elements in its implementation. It is concluded that Law Number 1 of 2023 represents a new direction providing stronger procedural guarantees for the right to life of death row inmates compared to the previous law, yet substantive protection remains conditional and non-absolute, reflecting the ongoing dilemma between law enforcement and human rights in Indonesia.